2015
DOI: 10.1155/2015/925987
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Ameliorates the Coronary Occlusion Related Tachycardia and Hypotension in Acute Rat Myocardial Ischemia Model: Potential Role of Hippocampus

Abstract: Mechanisms for electroacupuncture (EA) in disease treatments are still enigmatic. Here, we studied whether hippocampus was involved in the protection of EA stimulation on myocardial ischemia injury. Acute myocardial ischemia (AMI) model was produced. EA stimulation at heart meridian from Shenmen (HT7) to Tongli (HT5) was applied to rats 3 times a day for continuous three days. Coronary occlusion related tachycardia and hypotension, indicated by heart rate, mean arterial pressure, and rate pressure product, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…The hippocampus is a critical brain structure for memory and cognition as well as cardiovascular function. Cognitive de cits have been reported in patients with cardiovascular disease [36][37][38]and heart failure patients exhibit damage to the hippocampus [39,40].We previously showed that the mechanism by which acupuncture alleviates AMI-induced damage in the hippocampus is through synergistic action of the paraventricular nucleus, which regulate the sympathetic nerve and the solitary tract nucleus, which regulates the vagus nerve [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hippocampus is a critical brain structure for memory and cognition as well as cardiovascular function. Cognitive de cits have been reported in patients with cardiovascular disease [36][37][38]and heart failure patients exhibit damage to the hippocampus [39,40].We previously showed that the mechanism by which acupuncture alleviates AMI-induced damage in the hippocampus is through synergistic action of the paraventricular nucleus, which regulate the sympathetic nerve and the solitary tract nucleus, which regulates the vagus nerve [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…And cognitive dysfunction due to AMI in adult mice was correlated with decreases in reactive gliosis and neurogenesis in the hippocampus [11]. In our previous work, we showed that EA alleviates AMI in the hippocampus via regulation of the autonomic nervous system speci cally through the synergistic regulation of the sympathetic and vagus nerves by the hippocampal paraventricular nucleus and solitary tract nucleus, respectively [12][13][14]. These results suggest that the hippocampus is an important central brain structure mediating the positive effects of EA following AMI.…”
Section: Introductionmentioning
confidence: 99%
“…It usually occurs under strenuous exercise or emotional stress, lasting for a few minutes, and relieves itself after rest. Wu finds EA stimulation at HT7 (Shenmen-point), HT6 (Yinxi-point) and HT5 (Tongli-point) protects against the adverse impact on the cardiac function from hippocampus neuron, and improve the abnormal state of the heart function induced by MI, including heart rate, mean arterial pressure and rate pressure product [55]. According to modern medicine theory, MI is caused by coronary artery stenosis [51], and the pathogenesis of "thoracic obstruction" and "precordial pain" is blood vessel, in which the blood and qi circulate, impassability [52].…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemistry of ER and PR expressions were conducted following the previous publication [13]. The primary antibodies against ER (1:200) and PR (1:200) were from Abcam (USA).…”
Section: Immunohistochemistrymentioning
confidence: 99%